Imaging the Facial Nerve: A Contemporary Review - Sachin Gupta; Francine Mends; Mari Hagiwara; Girish Fatterpekar; Pamela C. Roehm (Radiology Research and Practice)
Imaging plays a critical role in the evaluation of a number of facial nerve disorders. The facial nerve has a complex anatomical course; thus, a thorough understanding of the course of the facial nerve is essential to localize the sites of pathology. Facial nerve dysfunction can occur from a variety of causes, which can often be identified on imaging. Computed tomography and magnetic resonance imaging are helpful for identifying bony facial canal and soft tissue abnormalities, respectively. Ultrasound of the facial nerve has been used to predict functional outcomes in patients with Bell’s palsy. More recently, diffusion tensor tractography has appeared as a new modality which allows three-dimensional display of facial nerve fibers.